Presentation - Hipólito, Rodrigo (Revista do Colóquio, 2024)
Journals such as Colóquio provide a valuable space for works that not only reflect on the arts, but connect them to crucial contemporary issues, such as human rights, sustainability, climate change, political and social dissent, and technological transformations. This issue reaffirms this commitment, offering a wide variety of articles, visual essays, and experience reports that reflect the vitality and plurality of the field. We invite you to delve into the reflections proposed in this issue and to enjoy reading it as a moment of encounter between knowledge, experiences, and perspectives. Enjoy your reading!